The practice of soil reinforcing in Europe proceedings of the symposium The practice of soil reinforcing in Europe organised by the Tenax Group under the auspices of the International Geosynthetics Society and held at the Institution of Civil Engineers on 18 May 1995 - Ingold, T. S. (Thomas Telford, 1995)
Provides details of the materials, design considerations applications, and construction techniques employed in Europe. Topics covered include the development and use of polymetric reinforcement, basal reinforcement, the use of reinforced soil structures in landfill, and ballistic soil nailing.